ANALISIS TERJADINYA GAGAL BAYAR PADA KOPERASI SIMPAN PINJAM - Fitri Amanda; Nazwa Fatimah Az-Zahra; Nabila Aulia Adek Putri; Dwi Desi Yayi Tarina (Cahaya Ilmu Bangsa, 2024)
Cooperatives are one of the business entities that have long been established and developed in Indonesia. There are many types of cooperatives that have been operating in this country, one of which is a Savings and Loan Cooperative. A Savings and Loan Cooperative (KSP) is a non-bank financial institution engaged in finance with business activities that include accepting deposits and lending money to members. The default experienced by savings and loan cooperatives raises the question of whether this reflects the performance of the Ministry of Cooperatives and SMEs so that it can be considered a failure of the institution. In fact, a cooperative as a business entity should function to help its members save and achieve mutual prosperity. There are two (2) factors that inhibit default in savings and loan cooperatives, namely internal factors and external factors. The Cooperatives Act does not specifically mention legal protection for member deposits. However, the legal protection of member deposits before the problem occurs is seen in the existence of an agreement made by the Cooperative with the Member. If the agreement is not implemented by one of the parties then one of the parties can be sued in court (Article 1243 of the Civil Code).